The segetal vegetation of Kocaeli province (Turkey) - (:unkn) unknown (FOUNDATION ENVIRONMENTAL PROTECTION & RESEARCH-FEPR, 2007)
The segetal vegetation of Kocaeli province (Turkey) was found by using the Braun-Blanquet's method in this study. The study was carried out between 2003-2004, and a total of 222 cereal fields (wheat, oats, barley and corn) were searched. The aim of this study is analizing the segetal vegetation and classifying as associations in the cereal fields in Kocaeli Province. We have defined four associations in the result of this study. One of them is new for the scientific world, the four associations: 1. Hordeeto-Sisymbrietum orientalis 2. Onopordetum acanthii 3. Sclerochloa dura-Coronopus squamatus 4. Rumici conglomerati-Legousietum speculiveneris ass. nov.
Keywords: Kocaeli; phytosociolgy; Turkey